Pembelajaran Ansambel Vokal di Era Revolusi Industri 4.0 - Laura Megawaty Manalu; Richard Jr. Kapoyos (Program Studi Pendidikan Musik FBS UNP, 2022)
In the era of the industrial revolution 4.0, it has an impact on fast information. Since the beginning of 2020 until now, face-to-face activities are still limited due to the COVID-19 pandemic. This has had an impact on the education system, particularly in the field of vocal music. But of course it takes creativity and innovation to overcome these problems. This study uses a qualitative approach. In writing this is qualitative data, using a descriptive approach, namely research that intends to make a description of situations or events (Basrowi, 2008). Based on data sources, this type of research is field research in the form of descriptive qualitative research. The form of vocal ensemble learning in the era of the industrial revolution 4.0 can be done by utilizing several digital applications. Among them, using the Zoom Meeting application by utilizing the video call feature and the use of features from Zoom have their respective advantages and this provides a new paradigm if both are used in the online vocal ensemble practice learning process.